Advances in magnetic resonance. - Waugh, John S. (Academic Press, 1965)
Advances in Magnetic Resonance, Volume 1, discusses developments in various areas of magnetic resonance. The subject matter ranges from original theoretical contributions through syntheses of points of view toward series of phenomena to critical and painstaking tabulations of experimental data. The book contains six chapters and begins with a discussion of the theory of relaxation processes. This is followed by separate chapters on the development of magnetic resonance techniques for studying rate processes in chemistry and the application of these techniques to various problems; the geometri.